The demographic, sexual health and behavioural correlates of Mycoplasma genitalium infection among women with clinically suspected pelvic inflammatory disease. Issue 1 (24th August 2009) - Short, V L; Totten, P A; Ness, R B; Astete, S G; Kelsey, S F; Murray, P; Haggerty, C L
Abstract : Objective: Mycoplasma genitalium has been identified as a cause of pelvic inflammatory disease (PID), a clinical syndrome associated with inflammation of the female upper genital tract and serious reproductive sequelae. As the demographic, behavioural and sexual risk profile of women with M genitalium -associated PID is not well understood, the characteristics of M genitalium -infected women presenting with clinically suspected PID were investigated. Methods: Data from 586 participants in the PID Evaluation and Clinical Health Study were analysed. Demographic, sexual history and behavioural characteristics, including age, race, marital status, education level, sexual activity, number of sexual partners, history of sexually transmitted infection (STI), bacterial vaginosis and PID, contraception use, oral and anal sex, age at sexual debut, douching practices and drug, alcohol and tobacco use, were compared between 88 women testing positive and 498 women testing negative for M genitalium by PCR in the cervix and/or endometrium. Twenty-two women with M genitalium mono-infections were compared with 172 women who tested positive for Neisseria gonorrhoeae by culture and/or Chlamydia trachomatis by PCR. Results: Age under 25 years, douching two or more times per month and smoking were independently associated with M genitalium . Women with M genitalium mono-infections were significantly less likely to be African-American (59.1% vs 86.0%, p = 0.001) than women with N gonorrhoeae and/or C trachomatis . Conclusions: Women infected with M genitalium had some characteristics commonly associated with PID and other STI. The demographic, sexual and behavioural characteristics of M genitalium -positive women were similar to women with chlamydial and/or gonococcal PID.